Enhancement of Cell Surface Expression and Receptor Functions of Membrane Progestin Receptor α (mPRα) by Progesterone Receptor Membrane Component 1 (PGRMC1): Evidence for a Role of PGRMC1 as an Adaptor Protein for Steroid Receptors - Peter Thomas; Yefei Pang; Jing Dong (2014)
A variety of functions have been proposed for progesterone receptor membrane component 1 (PGRMC1), including acting as a component of a membrane progestin receptor and as an adaptor protein. Here we show that stable overexpression of human PGRMC1 in nuclear progesterone receptor (PR)-negative breast cancer cell lines causes increased expression of PGRMC1 and membrane progesterone receptor α (mPRα) on cell membranes that is associated with increased specific [(3)H]progesterone binding. The membrane progestin binding affinity and specificity were characteristic of mPRα, with a Kd of 4.7 nM and high affinity for the mPR-specific agonist, Org OD 02-0, and low affinity for corticosteroids. Progestin treatment caused activation of G proteins, further evidence for increased expression of functional mPRs on PGRMC1-transfected cell membranes. Immunocytochemical and coimmunoprecipitation studies showed a close association of PGRMC1 with mPRα in cell membranes. Transfection of PGRMC1 into spontaneously immortalized rat granulosa cells was associated with membrane expression of PGRMC1 and mPRα as well as antiapoptotic effects of progestins that were abolished after cotransfection with small interfering RNA for mPRα. These data demonstrate that PGRMC1 can act as an adaptor protein, transporting mPRα to the cell surface, and that the progestin binding and apoptotic functions previously ascribed to PGRMC1 are dependent on cell surface expression of mPRα. Collectively, the results suggest PGRMC1 and mPRα are components of a membrane progesterone receptor protein complex. Increased expression of estrogen receptor β was also observed in the membranes of PGRMC1-transfected cells, suggesting that PGRMC1 can act as an adaptor protein for multiple classes of steroid receptors.